Utility of multimodality molecular profiling for pediatric patients with central nervous system tumors. Issue 1 (10th March 2022) - Rajappa, Prajwal; Eng, Kenneth W; Bareja, Rohan; Bander, Evan D; Yuan, Melissa; Dua, Alisha; Bhanu Maachani, Uday; Snuderl, Matija; Pan, Heng; Zhang, Tuo; Tosi, Umberto; Ivasyk, Iryna; et al.
Abstract: Background: As our molecular understanding of pediatric central nervous system (CNS) tumors evolves, so too do diagnostic criteria, prognostic biomarkers, and clinical management decision making algorithms. Here, we explore the clinical utility of wide-breadth assays, including whole-exome sequencing (WES), RNA sequencing (RNA-seq), and methylation array profiling as an addition to more conventional diagnostic tools for pediatric CNS tumors. Methods: This study comprises an observational, prospective cohort followed at a single academic medical center over 3 years. Paired tumor and normal control specimens from 53 enrolled pediatric patients with CNS tumors underwent WES. A subset of cases also underwent RNA-seq (n = 28) and/or methylation array analysis (n = 27). Results: RNA-seq identified the driver and/or targetable fusions in 7/28 cases, including potentially targetable NTRK fusions, and uncovered possible rationalized treatment options based on outlier gene expression in 23/28 cases. Methylation profiling added diagnostic confidence (8/27 cases) or diagnostic subclassification endorsed by the WHO (10/27 cases). WES detected clinically pertinent tier 1 or tier 2 variants in 36/53 patients. Of these, 16/17 SNVs/INDELs and 10/19 copy number alterations would have been detected by current in-house conventional tests including targeted sequencing panels. Conclusions: Over a heterogeneous set of pediatric tumors, RNA-seq and methylation profiling frequently yielded clinically relevant information orthogonal to conventional methods while WES demonstrated clinically relevant added value primarily via copy number assessment. Longitudinal cohorts comparing targeted molecular pathology workup vs broader genomic approaches including therapeutic selection based on RNA expression data will be necessary to further evaluate the clinical benefits of these modalities in practice.